Effects of the Piston Skirt’s Surface Structure on Coating Quality and Friction Functions - Zhang, Jian; Guo, Shenggang; Xiong, Peiyou; Li, Yanjun; Sun, Weitao; Deng, Lijun (Coatings (Basel), 2024)
It is necessary to take effective ways to reduce friction and wear grading of a friction pair for the purpose of improving the thermal efficiency and operating reliance of the internal combustion engine. As an effective way, coordinated multi-scaling structure optimization has gained more and more attention, however, its effect on coating adhesion strength remains unclear, and there is less systematic research on its interactive role in friction properties. The paper takes advantage of the stretching test and dynamic simulation calculation to study the influence of piston skirt waviness on coating adhesion as well as profile, waviness, and roughness on friction and wear performance. The research results show that coating adhesion strength will increase first and then decrease in the conditions of enlarging waviness depth, width, and roughness; in addition, surface roughness could generate a bigger effect on coating adhesion than waviness shape. Increasing the waviness width also reduces friction losses and wear in the piston skirt. When the waviness width increases from 0.25 mm to 0.40 mm, the friction losses of the piston skirt decrease by 27%, and the cumulative wear load on the skirt is reduced by 26%. However, under conditions of limited lubrication, smaller waviness widths are more effective in reducing wear. Additionally, increased roughness has a negative impact on the friction and wear characteristics of the piston skirt. This study provides valuable guidance for optimizing designs aimed at reducing friction and wear in internal combustion engine pistons and other mechanical components subject to friction and wear.